HAIKU FABLE: A SEM IOTIC SYNTHESIS IN AESOP‟S “A RAVEN AND A SWAN - Mohammed, RaedFadhil; HasanMousa, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
If semiotics is the epistemic discipline that fundamentally deals with the nature, function, and application of signs, symbols, and sign networks, in addition to being the philosophy of language whose quest is meaning-making, fable, then, is that literary domain that construes syntagmatic-paradigmatic constituents to produce a form of meaning. The study purports to investigate Aesop’s ” A Raven and a Swan” as a short narrative based on semiotic synthesis. The structural – semiotic approach articulated here is basically emanated from Saussure’s semiotic paradigm. The study embarks on the hypothesis that the semiotic structure of Aesop’s ”A Raven and a Swan” is a haiku narrative context. This study aims at exploring the semiotic features of the fable characters in order to highlight the contradictory features of each sphere. Out of 88 fables of the Greek fabulist, A Raven and a Swan” will be chosen as data for semiotic scrutiny.